Relationship between Asymmetry Indices, Anthropometric Parameters, and Physical Fitness in Obese and Non-Obese High School Students - Monoem Haddad (5345357) (2022)
Impaired balance is associated with an increased risk of lower extremity injuries. The purpose of this study was to investigate the relationship between age, anthropometric measurement, and asymmetry index (AI) in an adolescent high school population. Twenty-six male students (15 ± 1.0 years) were randomly selected. Body composition, measurements of vertical jump height using a countermovement jump test (CMJ), and dynamic single stance balance using the Y-balance test (YBT), were collected over 4 weeks. Hierarchical multiple linear regression analyses were used as dimension reduction techniques in four different blocks to determine valid predictors for AIs. In the first regression analysis, controlling for age, body mass, height, and body mass index (BMI), the regression coefficient (B = 0.383, 95% confidence interval [CI] [0.088, 0.679], p < 0.05) associated with body fat indicated that with each additional unit of body fat, the YBT AI increased by 0.383 units. In the second regression analysis, controlling for age, body mass, and BMI, the regression coefficients associated with height (B = −1.692, 95% CI [−3.115, −0.269], p < 0.05] and body fat percentage (B = 0.529, 95% CI [0.075, 0.983], p < 0.05) indicated that with each additional unit of height or body fat percentage, the CMJ AI decreased by 1.692 units and increased by 0.529 units. Grouping participants based on body fat percentage had a significant effect on the AIs (p < 0.05) of the CMJ and YBT. The AI of the CMJ was 15% higher, and that of the YBT was 7% higher in non-obese students than obese students. These findings contribute to the knowledge of the local community and the emerging body of literature on motor skills and competence related to weight in this population. Other Information Published in: International Journal of Environmental Research and Public Health License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://doi.org/10.3390/ijerph191710533